Models of body and femininity in a local gym - Tristán, Bianca (2011)
The purpose of this work is to explore the ideals of body and behavior among adult women of our new Peruvian middle class attending a gym. It suggests that the ideals of bodies developed in this place are in closely related to traditional notions of gender roles of our society. But, at the same time, emphasizes the fact that they, not only try to have a body in accordance to social expectation, but also to interact or make friends, and to experience a variety of emotions in performing aerobic activity itself. Finally, the paper explores the meaning that these women give to their experience at the gym. Not only does this experience get them closer to the ideal body, fixed by the social standards of femininity, but the experience turns into an opportunity to discuss and remake those models of femininity, and assert their own discourses of identity.